Efficacy of Intravenous Tenecteplase Bridge Thrombectomy for Recurrent Ischemic Stroke Within 3 Months: A Case Report - Liu C; Liu J; Ren H; Xu Y; Liu W (International Medical Case Reports Journal)
Cuicui Liu, Junyan Liu, Huiling Ren, Yuzhu Xu, Wanhu Liu Department of Neurology, The Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of ChinaCorrespondence: Wanhu Liu, Department of Neurology, The Third Hospital of Hebei Medical University, 139 Ziqiang Road, Shijiazhuang, 050000, People’s Republic of China, Email 22034101068@stu.hebmu.edu.cnAbstract: In the previous guideline recommendations, patients who have had a stroke within 3 months are excluded from intravenous thrombolysis (IVT) regimens. Some studies have suggested that IVT with alteplase (rt-PA) may be effective and safe in such patients, but evidence supporting the use of tenecteplase (TNK) is not sufficient. This paper includes an 80-year-old male patient readmitted for recurrence of ischaemic stroke (IS) after 48 days, who received TNK IVT as a bridging therapy prior to thrombectomy, with favourable results at 8-week follow-up. This case highlights that TNK alone or IVT as a bridging therapy prior to thrombectomy can also benefit patients with recurrent stroke within 3 months.Keywords: intravenous thrombolysis, recurrent ischemic stroke, tenecteplase